Calcium and L-glutamate present the opposite role in managing arsenic in barley. (15th March 2023) - Zeng, Fanrong; Nazir, Muhammad Mudassir; Ahmed, Temoor; Noman, Muhammad; Ali, Shafaqat; Rizwan, Muhammad; Alam, Mohammad Shah; Lwalaba, Jonas Lwalaba Wa; Zhang, Guoping
Abstract: Arsenic contamination in agricultural soils has posed tremendous threat to sustainable crop production and human health via food chain. Calcium and Glutamate have been well-documented in metal(loid)s detoxification, but it is poorly understood how they regulate arsenic-induced toxicity to plants. In this study, the effect of glutamate and calcium at high concentration on arsenic toxicity and accumulation in barley seedling was accessed in terms of plant growth, photosynthetic efficacy, arsenic uptake, translocation and accumulation, antioxidant defense, nutrient uptake and the expression of As transporters. Our results have demonstrated that calcium could effectively ameliorate arsenic toxicity to barley seedlings, which is mainly attributed to its beneficial effect on increasing nutrient uptake, reducing the aboveground arsenic accumulation and enhancing antioxidative defense capacity. However, it is unexpected that glutamate considerably exacerbated the arsenic toxicity to barley seedlings. More importantly, for the first time, glutamate was observed to tremendously facilitate the root-to-shoot translocation of arsenic by 41.8- to 60.8-fold, leading to 90% of the total amount of As accumulating in barley shoots. The reason of this phenomenon can be well explained by the glutamate-triggered enormous upregulation of genes involved in arsenic uptake ( HvPHT1;1, HvPHR2 and HvNIP3;2 ), reduction ( HvHAC1;1 ), translocation ( HvABCC7, HvNIP1;1 and HvNIP3;3 ) and intracellular sequestration ( HvABCC1 ). These findings suggest that calcium and glutamate function as the opposite player in managing arsenic, with calcium being an effective alleviator of arsenic stress to ensure the safe production of crops; while glutamate being a highly efficient phytoextraction agent for phytoremediation of arsenate-contaminated soils. Graphical abstract: Image 1 Highlights: Glutamate exacerbates arsenic toxicity and accumulation in barley. Glutamate extremely facilitates the acro-petal arsenic translocation in barley. Glutamate considerably upregulates arsenic transporters in barley roots. Calcium is beneficial to minimize arsenic toxicity and accumulation in barley.